Construction of perceptions, method and results: case of the sanitation sector - Pastor Paredes, Oscar (2023)
Knowing the perception of a person regarding a specific topic is relatively simple, the construction of the perception on a specific sector is a complex task that requires ad hoc methodologies and knowledge of statistical instruments that facilitate the processing of specialized opinions. The research article proposes a method and techniques to build the perception of the Peruvian sanitation sector, perfectly applicable to any public or private sector, as an alternative or complement to other methods available to the academy. The knowledge base line, necessary for the design of research tools, is built from the specialized bibliography. The research presents the research methodology, collection and analysis of fi eld information (in-depth surveys of key actors), and practical examples in each of its stages. The result is a proposal for collective sectoral perception, which aims to cover a wide range of related topics.